The Effect of SBSN, ISSI, Inflation and BI 7 DAY REPO Rate Toward Net Asset Value of Islamic Mutual Funds in 2016-2019 - Ovi Ariyanti (Journal of Islamic Business and Economic Review, 2020)
This research aimed to analyze the effect of SBSN, ISSI, Inflation and BI 7 Day Repo Rate toward Net Asset Value (NAB). Data used in this research were data of 2016-2019. The research method used multiple linear regression using Eviews 9 data processing. The results of the research showed that the t-test statistic of SBSN and ISSI had a positive effect toward NAV with probability values of 0.0462 and 0.0000 <0.05. BI 7 Day Repo Rate had a negative effect with a probability value of 0.0365 <0.05. Furthermore, for inflation, it had no effect toward NAV because the probability was 0.3159> 0.05.